2022
DOI: 10.1002/14651858.cd010260.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Hysterectomy with radiotherapy or chemotherapy or both for women with locally advanced cervical cancer

Abstract: BackgroundThis is an update of the Cochrane Review published in Issue 4, 2015. Cervical cancer is one of the most frequent cause of death from gynaecological cancers worldwide. Many new cervical cancer cases in low-income countries present at an advanced stage. Standard care in Europe and the US for locally advanced cervical cancer (LACC) is chemoradiotherapy. In low-income countries, with limited access to radiotherapy, LACC may be treated with chemotherapy and hysterectomy. It is not certain if this improves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Among these, the combination of surgical procedures and radiotherapy is a commonly utilized clinical approach for treating CC ( 21 ). Radiation therapy can potentially increase survival rates, enhance quality of life, and reduce adverse effects in patients with CC ( 22 ). Nonetheless, numerous clinical studies have uncovered variations in patients’ innate sensitivity to radiation, particularly among those with early or advanced cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the combination of surgical procedures and radiotherapy is a commonly utilized clinical approach for treating CC ( 21 ). Radiation therapy can potentially increase survival rates, enhance quality of life, and reduce adverse effects in patients with CC ( 22 ). Nonetheless, numerous clinical studies have uncovered variations in patients’ innate sensitivity to radiation, particularly among those with early or advanced cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Following the 2018 FIGO criteria, all patients with positive pelvic lymph nodes were re-staged to cervical cancer stage IIIC1p and underwent postoperative concurrent chemoradiotherapy (CCRT). The following criteria were used for exclusion ( 1 ): chemotherapy before surgery or radiotherapy ( 2 ), LNM in the para-aortic region ( 3 ), concurrent presence of other tumors ( 4 ), distant metastasis, and ( 5 ) no follow-up data. In this study, we collected data from patients with stage IIIC1p cervical cancer regarding LNM (including common iliac lymph node, number of LNM sites, the number and ratio of LNM), para-aortic lymph nodes (PALN) resection, vaginal brachytherapy utilization, type of radicality, postoperative high-risk factors (surgical margins and parametrial infiltration), intermediate-risk factors (tumor size, lymph-vascular space invasion [LVSI], depth of stromal invasion [DSI]), preoperative tumor markers (squamous cell carcinoma antigen [SCCA] and carcinoembryonic antigen [CEA]), adjuvant treatment regimens (CCRT and CCRT+ adjuvant chemotherapy [AC]), monocyte-to-lymphocyte ratio (MLR), and chemotherapy protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Radical hysterectomy and lymph node dissection are crucial for patients during the early stages. However, based on existing randomized controlled trials, we found insufficient evidence to suggest that hysterectomy improves the survival of women with locally advanced cervical cancer treated with either radiotherapy or chemoradiotherapy ( 4 ). The chances of pelvic LNM in cervical cancer stages IB2, IIA, and IIB were 11%, 13%, and 16%, respectively ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Divergent studies have reported variable outcomes. Some studies indicate that surgery may yield overall survival (OS) rates comparable to those achieved with CCRT [ 7 10 ]. In contrast, others indicate worse survival outcomes with surgical approaches [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%